APLIKASI PEMESANAN LAUNDRY BERBASIS SMS GATEWAY - Felicia Sylviana; Sherly Christina; Sunartie (JURNAL TEKNOLOGI INFORMASI, 2019)
Keywords : website, waterfall method, SMS Gateway application The development of information technology lately has entered almost all areas of our life. One of them in the field of business service provider of washing clothes or usually called the laundry. Each laundry business have its own way to improve their laundry service. In conveying information or promoting the Laundry to the community still using a manual way, and it takes very long time. So, it takes more time to get information. To able overcome these problems it is necessary to build a laundry booking application based sms gateway in Palangka Raya. Methodology The development of this application uses the  waterfall methodology, with the following stages, the first stage is the requirements analysis described using UML 2.5 (Unifer Modeling Language), the second stage is design, the third stage is coding and testing, the testing used is using blackbox, the fourth stage is implementation, the fifth stage is maintenance. From the results of application testing, it can be concluded that this application has functioned well by providing features such as features of laundry booking based SMS Gateway and laundry profile information that contains services found in laundry.